Water resources analysis of the Rječina karst spring and river (Dinaric karst) - Bonacci, Ognjen; Oštrić, Maja; Roje Bonacci, Tanja (Acta Carsologica, 2018)
The paper deals with complex hydrological/hydrogeological behaviour in the Rječina karst spring and river basin located in the north-western part of the deep and developed Croatian Dinaric karst. The Rječina Spring is one of the major karst springs in Croatia, used for water supply of Rijeka City and its surrounding area. Beside the use of Rječina spring for water supply, the development of the Rijeka hydroelectric power plant (HEPP) also changed hydrological and hydrogeological regime of the whole catchment. In order to analyse the anthropogenic influences in the system, hydrological analysis of the Rječina river and spring discharge was done, as well as the analysis of the available data of groundwater measurements. The analysis showed that, due to the increase of water caption and decrease of precipitation, the average annual spring discharge decreased for approximately 25% in the 1980-2016 period. Detailed analysis of groundwater measurements indicated aquifer behaviour and the need for additional measurements and catchment delineation. Key words: hydrology, hydrogeology, karst, Rječina Spring, Rječina River, Dinaric karst. Analiza vodnih virov kraškega izvira in reke Rječina (Dinarski kras) Članek obravnava zapletene hidrološke/hidrogeološke razmere v zaledju kraškega izvira in reke Riečine v severozahodnem delu globokega in dobro razvitega hrvaškega Dinarskega krasa. Izvir Rječina je eden največjih kraških izvirov na Hrvaškem, zajet je za oskrbo s pitno vodo za mesto Reka in njeno okolico. Poleg rabe izvira Rječine za oskrbo z vodo je razlog za spremenjen hidrološki in hidrogeološki režim celotnega zaledja tudi gradnja hidroelektrarne Reka (HEPP). Za analizo antropogenih vplivov na sistem smo zato naredili hidrološko analizo pretokov reke in izvira Rječina pa tudi analizo razpoložljivih podatkov merjenja podzemne vode. Analiza je pokazala, da se je zaradi povečanja zajemanja vode in zmanjšanja količine padavin povprečen letni pretok izvira v obdobju 1980–2016 zmanjšal za približno 25 %. Podrobna analiza meritev podzemne vode je nakazala značilnosti delovanja vodonosnika ter pokazala potrebo po dodatnih meritvah in določitvi zaledja izvira. Ključne besede: hidrologija, hidrogeologija, kras, izvir Rječina, reka Rječina, Dinarski kras.